On a workflow model based on generalized communicating P systems - Balasko, Akos (Computer Science, 2016)
This paper introduces a new formal mathematical model for investigating workflows from dynamical and behavioural point of view. The model is designed on the basis of a special variant of the biology-inspired formal computational model called membrane systems, where the jobs or services are represented by membrane objects whose behaviour is defined by communication and generalization rules. The model supports running computations in a massive parallel manner, which makes it ideal to model high throughput workflow interpreters. Among the variants introduced in the literature, we have selected the Generalized Communicating P Systems, as it focuses on the communication among the membranes. Most of the workflow languages, based on different formal models like Petri nets or Communicating Sequential Processes, support several predefined structures – namely workflow patterns – to control the workflow interpretation such as conditions, loops etc. In this paper we show how these patterns are adapted into the membrane environment which, taking into account that membrane systems can be used to study complex dynamic systems’ runtime behaviour, makes this model a relevant alternative for the current models